2011
DOI: 10.1021/jp206441u
|View full text |Cite
|
Sign up to set email alerts
|

Nonstatistical Dopant Distribution of Ln3+-Doped NaGdF4 Nanoparticles

Abstract: Lanthanide-based nanoparticles have many optical applications such as biolabels, lasers, optical amplifiers, and opticaldisplay phosphors. 1À11 These applications are generally accomplished by doping emissive Ln 3+ ions into an optically inactive matrix, such as fluoride, 12 phosphate, 13 oxide, 14 or vanadate, 15 so that maximum optical efficiency can be achieved. 16 Recently, Gd 3+ -based nanoparticles have been reported as magnetic resonance imaging (MRI) contrast agents because one nanoparticle easily cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 51 publications
5
57
0
Order By: Relevance
“…For now we assume that Γ rad and Γ Q are the only decay pathways for the luminescent centers. Assuming that the dopant centers are homogeneously distributed within the NC (which may in fact be not exactly true), 40 we obtain the expected decay dynamics of an ensemble of doped NCs by integrating Γ Q over the NC volume:where a and V are the radius and volume of the luminescent core of the NC, respectively,is the monoexponential radiative decay component (eq 3), andis the multiexponential solvent-quenching component to the decay (eq 2). …”
Section: Resultsmentioning
confidence: 99%
“…For now we assume that Γ rad and Γ Q are the only decay pathways for the luminescent centers. Assuming that the dopant centers are homogeneously distributed within the NC (which may in fact be not exactly true), 40 we obtain the expected decay dynamics of an ensemble of doped NCs by integrating Γ Q over the NC volume:where a and V are the radius and volume of the luminescent core of the NC, respectively,is the monoexponential radiative decay component (eq 3), andis the multiexponential solvent-quenching component to the decay (eq 2). …”
Section: Resultsmentioning
confidence: 99%
“…In the simplest case, the electric field may result from uncoordinated Eu 3+ and Y 3+ ions present on the NPs surface. We also need to take into account that the distribution of dopant ions is not statistical within the NP volume (Dong et al 2011). For this reason, we have decided to assume equal surface charge density ( Q surface ) for all types of investigated NPs, and thus roughly even electric field strength F z , at a fixed distance from the NPs surface, for all three types of investigated NPs.…”
Section: Resultsmentioning
confidence: 99%
“…The high sensitivity (down to ppm) of this technique, combined with the ability to measure the surface structure, makes this technique ideal for probing subtle variations on the surface of UC nanocrystals. 119,166,167 They found that the distribution of Y 3+ , Tb 3+ or Nd 3+ in the NaGdF 4 nanoparticles is inhomogeneous. 38,165 Depth-dependent composition measurement by XPS provides an alternative method to study the dopant distribution in UC nanocrystals.…”
Section: Xpsmentioning
confidence: 99%
“…64,124,171 For example, the replacement of Y 3+ in NaYF 4 by a trace amount of Gd 3+ can be readily confirmed by XPS measurement but not other techniques, including XRD and EDS. 165 They further extended this approach to characterizing core-shell UC nanocrystals by analyzing the relative signal intensity of lanthanides as a function of the photoelectron kinetic energy. By using synchrotron radiation, van Veggel and co-workers reported precise control over the penetration depth of X-rays in NaGdF 4 nanoparticles.…”
Section: Xpsmentioning
confidence: 99%